Is Older Age Associated with Higher Self- and Other-Rated ASD Characteristics? - Lever, Anne G. (J Autism Dev Disord, 2018)
Autism spectrum disorder (ASD) characteristics seem to abate over time, but whether this protracts until late adulthood is largely unknown. We cross-sectionally investigated self- and other-reported ASD characteristics of adults with (ASD: N(max-self) = 237, N(max-other) = 130) and without ASD (COM: N(max-self) = 198, N(max-other) = 148) aged 19–79 years. Within the ASD group, self-reported ASD characteristics, and sensory sensitivities were highest in middle adulthood, while age was not associated to empathy. Sex differences were also found. However, age-and sex-related differences were not revealed by others and self- and other-report were poorly concordant. These results show that ASD characteristics in adulthood are differently perceived across age, sex, and informants and suggest that it is important to repeatedly assess self-reported ASD characteristics during adulthood. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10803-017-3444-2) contains supplementary material, which is available to authorized users.